RESISTANCE AGAINST SPINOSAD IN A LAB-REARING Plutella xylostella POPULATION AND ITS IMPACT ON FITNESS COST - N. A. M. Ishadi; M. Norida; D. Omar; L. W. Hong2. (Journal of Animal and Plant Sciences, 2022)
Plutella xylostella commonly known as diamondback moth (DBM), is a polyphagus pest and has the ability to confer resistance and cross resistance to a number of insecticides. This experiment investigated the resistance development in DBM against spinosad and its implication on the fitness cost of the DBM population. A field strain of diamondback moth was collected from an organic farm in Semenyih, Selangor, Malaysia. Selection of DBM with spinosad, a spinosyn class of insecticide within 15 generations resulted in 42.81-fold resistance ratio (490.63 ppm at 15th generation (G15) compared to 11.5 ppm of parent (P) generation). Survival rate of 1st and 2nd instars was significantly higher in susceptible (SS) strain than in spinosad –selected (Spi-Sel) strain. Immatures of Spi-Sel strain took significantly shorter time to develop. Spi-Sel strain had high fitness cost i.e., low fitness (relative fitness = 0.25) in the absence of spinosad. In the absence of insecticide exposure, spinosad resistance accompanied by high fitness cost had adverse effect on the development and biological performance of the resistant strain. The results obtained provide a current understanding in resistance of spinosad after approximately 20 years of its introduction in the agriculture market and therefore, provides a new insight in resistance study of the insecticides with novel mode of action.
Keywords: Diamondback moth; fitness cost; resistance; selection; Spinosad